The Midlands State University trip scheduling system - Masango, Ruvimbo (Midlands State University, 2018)
The main purpose of this study was to design an online system which helps operations done by the work related learning office by allowing students to send their placement forms online, departmental coordinators to allocate lecturers students for supervision fairly, decrease the use of flat files in keeping students’ details and avoiding situations of overbooking of buses that transport the lecturers to assessments trips. The research adopted a descriptive survey design which was concerned in gathering information on how all the operations relating to work related learning are carried out by the university. Data was collected from about 20 to 30 respondents through questioners and interviews. Participatory observations were used. Major findings of the study were that the university because of its practices in work related learning attending students is at about 87% as there is need for fully making a student be aware of the dates that assessments will be done so because of this findings when put in statically proved that the university is greatly doing successfully in the WRL section however there is need to fill out the loophole of computerizing on the manual system that is being used. As a recommendation, the organization may consider introducing more computerized solutions to replace the existing manual processes in order to improve the efficiency of its operations. There is a scope for further research on employing the use of using sms technology in the organization. There are certain areas that require sound security measures and therefore by using smartcard technology, access keycards can be made for authorized personnel which will control access to these areas.